Faktor-Faktor yang Mempengaruhi Niat Mahasiswa untuk Melakukan Pengungkapan Kecurangan (Studi Empiris Pada Mahasiswa Program Studi D-IV Akuntansi Keuangan Publik Angkatan Tahun 2017-2019) - M. Fauzul Shodiq; Rosmida Rosmida (Jurnal IAKP: Jurnal Inovasi Akuntansi Keuangan & Perpajakan, 2022)
The purpose of this study was to determine (1) the effect of subjective norm factors on the intention of students of public financial accounting study program to disclose fraud (2) the influence of attitude factors on behavior on the intentions of students of public finance accounting study program to disclose fraud (3) influence of perceived control factors behavior on the intention of students of public financial accounting study program to disclose fraud (4) the influence of subjective norms, attitudes towards behavior, and perceptions of behavioral control on the intentions of public financial accounting students to disclose fraud. The type of data used in this research is quantitative data with quantitative methods. The results of this study indicate that (1) based on the results of testing hypothesis 1, it states that subjective norms have no significant effect on students' intentions to disclose fraud. Therefore, the first hypothesis testing was rejected. (2) based on the results of testing hypothesis 2, it is stated that attitudes towards behavior have a significant influence on students' intentions to disclose fraud. There fore the second hypothesis testing is accepted. (3) based on the results of testing hypothesis 3, it is stated that behavioral control has a significant effect on students' intention to disclose fraud. There fore the third hypothesis testing is accepted.Â